Struktur Komunitas Zooplankton di Bendungan Telaga Tunjung, Kabupaten Tabanan-Bali - Wahyudiati, Ni Wayan Desy; Arthana, I Wayan; Kartika, Gde Raka Angga (Journal of Marine and Aquatic Sciences; Vol 3 No 1 (2017), 2017)
Zooplankton are the heterotroph aquatic organisms and has a week swimming. Zooplankton acts as the first consumer in the waters, which utilize phytoplankton as their food. This research located in Telaga Tunjung reservoir, Timpag Village, Kerambitan Subdistrict, Tabanan Regency. The reservoir is used for industry, irrigation and tourism development. The aim of the research was to determine the community structure of zooplankton in Telaga Tunjung reservoir. This research was conducted from January to February 2016. Water sampling was conducted twice with a sampling interval of 2 weeks in 4 stations. There was a total of 23 species of zooplankton found, consisting of 6 classes: Eurotatoria (8 genera), Ciliatea (1 genera), Branchiopoda (4 genera), Monogononta (1 genera), Tubulinea (1 genera) and Maxillopoda (3 genera). The most common species of zooplankton found in the sampling station were Polyarthra vulgaris (3.04 ind/l), Anuraeopsis coelata (1.28 ind/l), Keratella valga (0.43 ind/l), Vorticella sp. (0.49 ind/l), Diaphanosoma brachyurum (0.28 ind/l), Nauplius sp. (0.16 ind/l) and Megacyclops viridis (1.16 ind/l). The average abundance of zooplankton was 9.38 ind/l. Based on the abundance of zooplankton, the trophic status of Telaga Tunjung reservoir is mesotrophic.
Keywords: community structure; mesotrophic; reservoir; zooplankton